Educating the Teachings of KH Ahmad Dahlan with Cinema: A Promising Strategy to Increase Student Peace - Saputra, Wahyu Nanda Eka; Faturrahman, Faturrahman (Buletin Konseling Inovatif, 2025)
This study aims to evaluate the effectiveness of cinema-based education inspired by KH Ahmad Dahlan's teachings in fostering peace among students. The research was conducted at Muhammadiyah Vocational High School 2 Yogyakarta, Indonesia using a quasi-experimental design, specifically a Pretest-Posttest Control Group Design. The study involved 14 students divided into two groups: an experimental group (7 students) that received the cinema-based education intervention and a control group (7 students) that did not receive any intervention. The peace scale that has a good level of reliability is used to measure the level of peace. The peace scale consists of 26 statement items that have been tested for validity. Hypothesis testing was conducted using the Mann-Whitney test to determine the significance of differences between the two groups. The results indicated a significant difference between the experimental and control groups, with the experimental group showing a greater improvement in peace scores following the intervention. These findings demonstrate that cinema-based education grounded in KH Ahmad Dahlan's teachings is effective in enhancing student peace.